PENGARUH PENGGUNAAAN MEDIA PEMBELAJARAN “EDUCANDY” UNTUK MENINGKATKAN KEMAMPUAN MENULIS BAHASA ARAB SISWA KELAS X B DI PONDOK PESANTREN AL-ROSYID BOJONEGORO - Reza Dwi Kurniawati; Aufia Aisa; Rina Dian Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Writing skills are essential in learning Arabic, as they require vocabulary mastery, grammatical rules, and the ability to organize ideas systematically. However, the writing skills of Class X B students at Al-Rosyid Islamic Boarding School (Pondok Pesantren) Bojonegoro remain low. This is evident from errors in sentence structure, limited vocabulary, and low learning motivation caused by conventional, less diverse teaching methods. Therefore, innovation in interactive learning media is needed, one of which is through the digital game Educandy. This study aims to determine the impact of using Educandy media on improving students' Arabic writing skills and to evaluate its effectiveness compared to conventional teaching methods. This research employed a quantitative approach conducted on a learning group. Data were collected through written tests (pre-test and post-test), observation, and documentation, and analyzed using paired sample t-test and independent sample t-test. The results indicated that the use of Educandy media significantly improved students' Arabic writing skills. Furthermore, Educandy enhanced learning motivation, active participation, and students' ability to expand vocabulary while composing sentences more accurately. Thus, Educandy media is proven effective as an innovative learning alternative for Arabic writing skills.